Evaluating technologies in automobile markets. (12th May 2004) - Roder, Alexander; Kypreos, Socrates; Wokaun, Alexander
A new approach has been developed for the comprehensive comparison of competing technologies. It combines two well-established tools: life-cycle assessment (LCA) and energy-engineering models (EEM). The approach has been applied to evaluate different car powertrains and fuels. The results show how the ranking of different technologies depends on assumptions and the value system of the decision-maker. Whereas conventional technologies and fuels dominate in a business-as-usual scenario, policies that take external costs into account foster alternative solutions. This is especially so for fuels from natural gas and biofuels, and the fuel cell powertrain is also favoured under these circumstances. The new approach of combining LCA and EEM has proved its usefulness for the support of decision-making. Nonetheless, limitations that could be overcome by further development become apparent, and are elaborated herein.